Inhibition of Lupus Anticoagulant Activity by Hexagonal Phase Phosphatidylethanolamine in the Presence of Prothrombin - Rauch, Joyce; Tannenbaum, Marion; Neville, Carolyn; Fortin, Paul R. (Thrombosis and Haemostasis, 1998)
We have previously demonstrated that lupus anticoagulant antibodies from patients with systemic lupus erythematosus (SLE) specifically recognize hexagonal (II) phase phosphatidylethanolamine (PE), but not bilayer PE (Thromb Haemost 1989; 62: 892). In those studies, the involvement of proteins in this recognition was not evaluated. To address this issue, we have isolated IgG lupus anticoagulant antibodies from the plasma of SLE patients and evaluated the inhibition of lupus anticoagulant activity by hexagonal (II) phase PE in the presence and absence of purified plasma proteins. All six of the IgG lupus anticoagulant antibodies tested were inhibited by hexagonal (II) phase PE in the presence, but not the absence, of human prothrombin. In contrast, little or no inhibition was observed with prothrombin alone or with PE in combination with either β2-glycoprotein I or annexin V. These data indicate that, for certain lupus anticoagulant antibodies, inhibition by hexagonal (II) phase PE is dependent on prothrombin, suggesting that these antibodies recognize a complex of PE and prothrombin.